Elimination of voltage harmonics caused by nonlinear loads in distributed power systems consisting of inverters - Parlak, Koray Şener; Özdemir, Mehmet; Aydemir, M. Timur (Praise Worthy Prize S.r.l, 2009)
This paper suggests the use of synchronous frame harmonic elimination technique in distributed power systems consisting of inverters with nonlinear loads. Inverters of the distributed system are controlled to share the active power. Power sharing is achieved without any communication between the units. To eliminate the harmonics caused by nonlinear loads, synchronous frame controller is used. The technique is explained in detail and simulation results for a system consisting of two inverters are given. The results show that the technique can be successful to eliminate the harmonics caused by nonlinear load while the active power sharing is achieved. © 2009 Praise Worthy Prize S.r.l. - All rights reserved.
Keywords: Distributed operation; Harmonic elimination; Load-frequency droop; Synchronous reference frame